2019
DOI: 10.21037/acs.2019.03.01
|View full text |Cite
|
Sign up to set email alerts
|

Robot-assisted thoracic surgery in Colombia: a multi-institutional initial experience

Abstract: Background: Robotic assisted videothoracoscopic surgery (RVATS) adoption has increased worldwide from 3.4% in 2010 to 17.5% in 2015. However, in Latin America, the literature is limited to a report of a series of 10 patients who underwent RVATS lobectomy and one case report of an RVATS thymectomy from Brazil. Methods: This is a retrospective review of all RVATS performed in Bogotá Colombia since 2012. A single thoracic surgeon (RB) performed all the operations at three institutions: Clínica de Marly, Fundación… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…In a series recently published by Terra et al, 250 cases were reported including not only lung resection but also mediastinal tumors resections and diaphragmatic plication (23,24). In 2019, Buitrago and Restrepo published the second series of RATS in Latin America, with 14 cases of pulmonary resections showing comparable perioperative results to other reports (25).…”
Section: Latin Americamentioning
confidence: 95%
“…In a series recently published by Terra et al, 250 cases were reported including not only lung resection but also mediastinal tumors resections and diaphragmatic plication (23,24). In 2019, Buitrago and Restrepo published the second series of RATS in Latin America, with 14 cases of pulmonary resections showing comparable perioperative results to other reports (25).…”
Section: Latin Americamentioning
confidence: 95%
“…As the pursuit of optimal and universal health care continues, the next step with regard to optimizing access to quality cardiac surgical care pushes more towards bundled payment models [ 7 ] . At the moment, robotic surgery in Colombia is still in its infancy, with only 5 centers in the country having robotic consoles, and only one center performing robotic cardiac surgery [ 1 - 3 , 5 ] . Throughout the years, cardiothoracic surgery in Colombia has grown following American footsteps and techniques.…”
Section: Commentsmentioning
confidence: 99%
“…Although Colombia began performing minimally invasive (MICS) and video-assisted cardiac procedures since the mid 1990s, they were not routine until 2010. With regard to advances in minimally invasive cardiothoracic surgery, the country has come a long way from long traditional incisions to video-assisted and minimally invasive cardiac and thoracic surgeries, robotic thoracic surgery in 2012, and uniportal video-assisted thoracoscopic surgery (VATS) in 2014 [ 1 - 3 ] . Although robotic cardiac procedures offer many advantages to patients, this approach is still finding its place, even in high-income countries.…”
Section: Introductionmentioning
confidence: 99%
“…The removal of an entire lung lobe is called a lobectomy, and video‐assisted thoracoscopic surgery (VATS) lobectomy has become a minimally invasive surgical procedure for lung cancer resection (Guido‐Guerrero et al., 2018 ; Nachira et al., 2018 ; Buitrago and Restrepo, 2019 ; Raveglia et al., 2019 ). It becomes a routine preparatory step that an indwelling urinary catheter is used to prevent intraoperative urinary retention (Van Backer et al., 2019 ) in VATS lobectomy.…”
Section: Introductionmentioning
confidence: 99%